Feasibility and usability of Kegel Exercise Pregnancy Training App (KEPT App) among pregnant women with urinary incontinence - Jaffar, Aida; Muhammad, Noor Azimah; Mohd Sidik, Sherina; Admodisastro, Novia; Abdul Manaf, Rosliza; Foo, Chai Nien; Suhaili, Nazhatussima (Multidisciplinary Digital Publishing Institute, 2022)
Pelvic floor muscle training (PFMT) is crucial to improving urinary incontinence (UI). This study aimed to assess the Kegel Exercise Pregnancy Training (KEPT) app’s feasibility and usability. This is a subgroup analysis from a researcher-blinded, randomised controlled pilot feasibility study among pregnant women with UI. The Malay version of the mHealth App Usability Questionnaire (Interactive) evaluated the app’s usability. Ten pregnant women completed the study, with mean age (SD) of 28.9 years (3.1). The app’s feasibility was rated above average. The app was reported with usable in all domains, (1) system information arrangement (4.98/7.0), (2) usefulness (4.89/7.0) and (3) ease-of-use and satisfaction (5.03/7.0). Education level was negatively correlated with the app’s feasibility (r = −0.81, p < 0.001) and all domains of usability such as ease-of-use (r = −0.66, p = 0.01), system information (r = −0.81, p = 0.001) and usefulness (r = −0.81, p = 0.001). PFMT video was among the app features chosen to be helpful. This study demonstrates that the newly developed user-centred design KEPT app is feasible and usable. However, the future app should provide direct feedback about their exercise techniques to motivate PFMT adherence.